Hubungan Tingkat Pengetahuan dengan Self Efficacy Vaksinasi COVID-19 di Puskesmas Tarus Kabupaten Kupang - Sumbayak, Anastasia Emma Reinaita; Koamesah, Sangguana Marthen Jacobus; Pakan, Prisca Deviani; Sagita, Sidarta (Universitas Nusa Cendana, 2023)
Background : The 2019 Corona Virus Disease pandemic is still a concern until today. The virus that causes COVID-19 can keep mutating and producing new variants over time. The government has attempted various health protocols including a national vaccination program, with the aim of forming herd immunity. Vaccination has 2 stages of primary vaccination and additional or booster dose of vaccination. Based on data from the Ministry of Health as of 19 January 2022, Kupang Regency has the lowest vaccination rate in East Nusa Tenggara. This can be caused by a lack of self efficacy or belief in receiving the COVID-19 vaccine. Several survey results show that people’s refusal and doubts about receiving vaccinations are due to concerns about the safety and effectiveness as well as the side effect of COVID-19 vaccine, which can be caused by lack of knowledge about the COVID-19 vaccination. Objective : This study aims to determine whether there is a relationship between the level of knowledge and self efficacy of COVID-19 vaccination at the Tarus Health Center, Kupang Regency. Method : This study used an analytical observational research design with a cross sectional design. Samples were choosen using a non-probability sampling technique with a type of consecutive sampling with a total sample of 103 people. The data were collected using a questionnaire on Knowledge of COVID-19 Vaccination and Self Efficacy of COVID-19 Vaccination to the visitors of Tarus Health Center, Kupang Regency. The data analysis used is the Rank Spearmen Correlation test. Result : From the test results using the Rank Spearman Correlation test, there was no significant correlation between the level of knowledge with the self efficacy of COVID-19 vaccination at the Tarus Health Center, Kupang Regency with the sig(2-tailed) > 0.005. Conclusion : There is no significant correlation between the level of knowledge with the self efficacy of COVID-19 vaccination at the Tarus Health Center, Kupang Regency.